Instrument validity: HIV and other sexually transmitted infections in homeless people - Anna Cláudia Freire de Araújo Patrício; Richardson Augusto Rosendo da Silva; Ivoneide Lucena Pereira; Luipa Michele Silva; Maria Alzete de Lima; Maria Amanda Pereira Leite; Maria Hellena Ferreira Brasil; Suzanna Valéria Oliveira Souza (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to validate, through the Item Response Theory, an instrument on vulnerability to HIV and other sexually transmitted infections in homeless people. Methods: a cross-sectional study carried out between February and May 2018 with 100 homeless people in a municipality in northeastern Brazil. A sociodemographic questionnaire was applied, and another with items referring to behaviors vulnerable to HIV and sexually transmitted infections (STIs). Subsequently, it was assessed through the Item Response Theory. Results: the items previous diagnosis of STIs (F=0.473), partner with STI symptoms (F=0.518), drug use (F=0.509), sex for money (F=0.552), STI symptoms (F=0.448), number of sexual partners (F=0.616), sharps sharing (F=0.398) and being a victim of sexual violence (F=0.347) were validated. Conclusions: the instrument proved to be validated, being able to identify vulnerability to HIV and other sexually transmitted infections in homeless people.